The Syriac tradition of the work of the Holy Spirit in the Church to make it One, Holy, Catholic and Apostolic - Aydin, Mor Polycarpus Augin (2018)
This article, by Mor Polycarpus, Syriac-Orthodox Metropolitan of the Netherlands, describes the Holy Spirit, through the use of metaphors from both Old and New Testaments, drawing attention to the close purposeful link between the Incarnation and the sending of the Holy Spirit at Penteost. It then continues, under the heading of "The Holy Spirit in Liturgy", to illustrate the teaching to believers and the revelatory role of the Holy Spirit in "Praise", "Prayer", "Pentecost Prayer" and "Eucharistic Liturgy", using illustrations from the treasure of poetry for which the Syriac-Orthodox Church's liturgy is renowned and which speaks so eloquently of the Spirit's role in the unity, holiness, catholicity and apostolicity of the Church.
Keywords: Holy Spirit; Pentecost; Syriac Eucharistic Anaphoras; Syriac-Orthodox Church; catholicity and apostolicity; Epiclesis; Holiness; Sanctification; Unity; worship in "spirit and in truth"